Nomenclatural changes in two families of asellote isopods (Acanthaspidiidae and Ischnomesidae) - Merrin, Kelly L.; Poore, Gary C. B. (Zootaxa, 2015)
Iolanthe Beddard, 1886a is shown to be a senior synonyn of Acanthaspidia Stebbing, 1893, the replacement name for the preoccupied Acanthoniscus Sars, 1879 (Isopoda: Asellota: Acanthaspidiidae). Ischnomesus kussakini nom. nov. is erected as a replacement name for Ischnomesus antarcticus (Kussakin, 1982), preoccupied in this combination (Isopoda: Asellota: Ischnomesidae).